Protecting our ports domestic and international politics of containerized freight security - Grillot, Suzette; Cruise, Rebecca J.; D'Erman, Valerie J. (Homeland security series, 2010)
Investigates the various issues surrounding the container security issue. This title analyzes cooperation between agents in the United States and abroad, explores the domestic and international politics of port security, and provides an assessment of fifteen of the world's sea ports.